KEBERLANJUTAN DAN TATA KELOLA: STUDI EMPIRIS ATAS HUBUNGAN PENGUNGKAPAN LINGKUNGAN, KEPEMILIKAN INSTITUSIONAL, DAN KINERJA PROFITABILITAS - Halimah, Elsa Nur; Kuswanto, Randy (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
This study aims to examine the impact of environmental disclosure and institutional ownership on profitability. This study takes a population of consumer cyclicals and consumer non-cyclicals companies, with listing qualifications on the Indonesia Stock Exchange in the period 2021 to 2023. This study involves the use of multiple regression analysis using SPSS software version 26. The sample was determined through purposive sampling which resulted in 60 business entities. From the results of data analysis, it is known that environmental disclosure has a positive impact on company profitability, while institutional ownership does not show a positive effect on company profitability.